Integrasi Ekonomi Islam dalam Revitalisasi Lumbung Pangan Masyarakat: Kajian Literatur - Ahmad Syahirul Alim (Diversity: Jurnal Ilmiah Pascasarjana, 2025)
Global food security faces serious challenges due to inter-country conflicts and climate change, which exacerbate food insecurity, particularly in developing countries such as Indonesia. The government has initiated various programs, such as national food reserves and the revitalization of community food reserves, to maintain food security. However, integrating Islamic economics into these policies has not been optimally utilized. This study uses a literature review to analyze Islamic economics's application in revitalizing community food reserves through philosophical, contextual, and practical approaches. The results indicate that community food reserves have a strong theological foundation from the Qur'an and Hadith and can be more effectively developed through Islamic economic instruments, such as zakat, infak, and sharia financing. The research recommendations include applying Islamic economic integration in managing community food reserves and developing an operational framework to support its implementation..